Pengaruh Kesenian Jathilan dan Joged Bumbung bagi Kehidupan Sosial Budaya Masyarakat: Studi Kasus pada Etnis Jawa dan Bali di Lampung, Indonesia - I Wayan Mustika; Putu Setyarini (Institut Seni Indonesia Denpasar, 2022)
The people of Lampung from the Balinese and Javanese tribes who inhabit the Seputih Banyak area of Central Lampung Regency have the arts of jathilanand joged bubungas part of their native arts. Both of these arts become the pride and can establish a close relationship in social life. To see the influence that exists in the arts of jathilanand joged bumbung, an ethnocoreological approach and a social system are used. Ethnochoreology is seen as capable of seeing, studying, and responding to various formsof regional dances from various tribes. Field and library methods are used to examine and examine the influence of these two arts in social relations. For this reason, the lives of the people of these two tribes are very tolerant in terms of art, social and culture. It is not surprising that this good social relationship until there are two folk arts of different types, origins, and cultures can be used as glue in social relations. Often in religious ceremonies, weddings, and national holidays this art appears. In the art performances, these two ethnic groups are always visited by both children, teenagers, and the elderly. Both jathilanand joged bubungperformances are in the form of an arena. The dancers are surrounded by spectators who can freely watch from anywhere. Jathilan art is generally performed in the afternoon until the evening, while joged bumbungis performed at night.